Pengaruh Fear of Missing Out (FoMO) dan Literasi Keuangan terhadap Keputusan Investasi: Studi Kasus Generasi Muda di Kota Karawang - Dean Dean Wicaksono; Rina Rina Maria Hendriyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Young people play a strategic role in economic growth, including in the development of investment in Indonesia. The characteristics of millennials and Gen Z, who are highly adaptable to technology, position them as key actors in increasing the number of investors, particularly in regions such as Karawang. This study aims to analyze the influence of Fear of Missing Out (FoMO) and financial literacy on investment decisions among young people in Karawang. A quantitative method with a multiple linear regression approach was used, involving data from 123 respondents who are active young investors. The results show that both FoMO and financial literacy have a significant influence on investment decisions. FoMO has a positive effect, indicating that the higher the level of FoMO, the greater the tendency for individuals to invest. Meanwhile, financial literacy also has a positive and significant effect, suggesting that strong financial understanding encourages rational and well-planned investment decisions. The implications of this study highlight the need for broader financial literacy education and greater awareness of psychological factors in financial decision-making, in order to foster healthy and sustainable investment behavior among the younger generation.